A STUDY ON THE COMPANY VALUE OF PUBLIC BANKS LISTED IN THE INDONESIAN STOCK EXCHANGE BETWEEN 2010 – 2015 - Muhajir, Atok; Miyasto, Miyasto; Mawardi, Wisnu (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
Company value that tends to decline is a problem that must be addressed. This is in line with the theory of company which mentions that the goal of a company is to maximize it value. This study is aimed at analyzing the effects of Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Income Diversification and Operational Cost and Return (BOPO) on company value, with Price Book Value (PBV) and Return on Asset (ROA) as intervening variables. The study population consists of companies listed on the Indonesian Stock Exchange between 2010 and 2015. The sampling technique employed was purposive sampling and 26 companies were sampled according to the pre-determined criteria. Analyzes were carried out using the SPSS program, with the data undergoing a statistical testing beforehand. Results from the first regression model show that LDR has positive and significant effect on ROA, BOPO has negative and significant effect on ROA, while NPL and Income Diversification does not have any effect on ROA. On the other hand, results from the second regression model show that LDR has negative and significant effect on PBV; Income Diversification has positive and significant effect on PBV, whereas NPL and BOPO do not have any effect on PBV. Statistically, this study also shows that ROA has a mediating effect on the relationship between Income Diversification and BOPO against PBV.